Effect of Carbonation-Treated Recycled Aggregates on the Properties of Permeable Geopolymer Concrete - Li, Hui; Jin, Chen; Wu, Lei; Yu, Xiaoqing (Journal of Asian Concrete Federation, 2025)
To address technical challenges such as the high water absorption of recycled aggregates (RA) and the lowmechanical performance of permeable concrete, this study systematically investigates the optimization of carbonationmodification processes for RA and their coupling mechanisms with geopolymer binder systems. By adjusting COconcentration and environmental humidity, the densification of RA was enhanced, resulting in a 24.6% reduction in waterabsorption and a 15.49% decrease in crushing value, significantly improving their applicability in green permeable concreteExperimental results demonstrated that carbonation treatment induced in situ deposition of calcium carbonate on aggregatesurfaces, effectively sealing microcracks and enhancing interfacial properties. The geopolymer concrete exhibited excellentpermeability and mechanical strength, with a maximum compressive strength of 52.1 Pa, while maintaining performanceconsistency under controled porosity (minor deviation from desien valuesl. Further analvsis revealed that ontimizecbinder compositions mitigated strength degradation caused by increased porosity and compensated for interfacial bondingdeficiencies in RA. Freeze-thaw cycle tests indicated that RA-based specimens exhibited poor durability, with accelerateddeterioration at higher porosity, while optimized binder formulations significantly enhanced frost resistance. A regressionmodel was established to quantify the effects of porosity and aggregate type on durability.